Courage – That’s What Was Needed. Romualdas Ozolas interviewed by Valdemaras Klumbys - Klumbys, Valdemaras (Problemos, 2018)
[tekstas lietuvių kalba]Romualdas Ozolas interviewed by Valdemaras Klumbys. Vilnius, July 8, 2002.Editing and Commentaries by Valdemaras Klumbys.Document: audiorecord (57 min.), privat collection of V. Klumbys.
Keywords: none